(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to analyze the legal consequences arising from patient consent to medical actions, as well as the legal actions that can be taken if there are violations in the consent process. This research uses a normative method, which relies on primary and secondary legal materials. The legal materials were obtained through literature studies, analysis of books, journals, and an approach to relevant laws and regulations. Based on the research results, it shows that medical consent has significant legal implications, particularly regarding the protection of patient rights. Non-compliance with valid consent procedures can lead to legal consequences in the form of civil liability for medical personnel or healthcare facilities. Furthermore, legal actions that can be taken by patients include filing a lawsuit for violations of rights, both through litigation or non-litigation channels. The recommendation of this study is for medical personnel and healthcare institutions to understand and comply with legal principles related to medical consent. This is important to ensure optimal legal protection for patients and to reduce legal risks that may arise from violations of patient rights. Abstrak: Penelitian ini bertujuan untuk menganalisis akibat hukum yang timbul dari persetujuan tindakan medis terhadap pasien, serta tindakan hukum yang dapat diambil apabila terjadi pelanggaran dalam proses persetujuan tersebut. Penelitian ini menggunakan metode normatif, yaitu penelitian yang mengandalkan bahan hukum primer dan sekunder. Bahan hukum diperoleh melalui studi kepustakaan, analisis referensi buku, jurnal, serta pendekatan terhadap peraturan perundang-undangan yang relevan. Berdasarkan hasil penelitian menunjukkan bahwa persetujuan tindakan medis memiliki implikasi hukum yang penting, khususnya terkait perlindungan hak-hak pasien. Ketidakpatuhan terhadap prosedur persetujuan yang sah dapat mengakibatkan akibat hukum berupa tanggung jawab perdata bagi tenaga medis atau fasilitas kesehatan. Selain itu, tindakan hukum yang dapat diambil oleh pasien mencakup pengajuan gugatan atas pelanggaran hak, baik melalui jalur litigasi maupun non-litigasi. Rekomendasi dari penelitian ini adalah agar tenaga medis dan institusi kesehatan memahami dan mematuhi prinsip-prinsip hukum yang terkait dengan persetujuan tindakan medis. Hal ini penting untuk memastikan perlindungan hukum yang optimal bagi pasien, serta mengurangi risiko hukum yang dapat timbul akibat pelanggaran terhadap hak pasien.